Somalia : Staff -Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key issues related to the economy of Somalia. Since 2012, Somalia has been recovering slowly from nearly 25 years of civil war. Weak institutional capacity, complex clan politics, and a challenging security situation have complicated economic reconstruction. As a result, social and economic conditions remain dire. To help Somalia's economic reconstruction efforts and establish a policy implementation track record as an important step toward an eventual fund arrangement, the authorities have requested an IMF staff-monitored program. It focuses on strengthening macroeconomic policy management and reforms to strengthen economic governance and institutional capacity and keep up the pace of restoring key economic and financial institutions.